The Prognostic Significance of Combined Pretreatment Fibrinogen and Neutrophil-Lymphocyte Ratio in Various Cancers: A Systematic Review and Meta-Analysis - Liu, Rongqiang; Zheng, Shiyang; Yuan, Qing; Zhu, Peiwen; Li, Biao; Lin, Qi; Shi, Wenqing; Min, Youlan; Ge, Qianmin; Shao, Yi (Disease Markers, 2020)
Purpose. The prognostic value of a new scoring system, termed F-NLR, that combines pretreatment fibrinogen level with neutrophil-lymphocyte ratio has been evaluated in various cancers. However, the results are controversial. The purpose of this study was to comprehensively analyze the prognostic value of F-NLR score in patients with cancers. Methods. An integrated search of relevant studies was conducted by screening the PubMed and Embase databases. Pooled hazard ratios, with 95% confidence intervals (CIs), for overall survival (OS) and disease-free survival (DFS)/progression-free survival (PFS) were calculated to estimate the prognostic significance of F-NLR score in patients with various tumors. A random effects model was used for comprehensive analysis, and subgroup and meta-regression analyses were used to explore sources of heterogeneity. Results. Thirteen articles reporting data from of 4747 patients were included in the study. Pooled analysis revealed that high F-NLR score was significantly associated with poor OS (HR=1.77; 95% CI, 1.51–2.08) and poor DFS/PFS (HR=1.63; 95% CI, 1.30–2.05). Subgroup and meta-regression analyses did not alter the prognostic role of F-NLR score in OS and DFS/PFS. Conclusions. Increased F-NLR score is significantly associated with poor prognosis in patients with cancers and can serve as an effective prognostic indicator.